Smoking: A Jewish view - Bulka, Reuven P. (Journal of religion and health, 1986)
The issue of smoking and Jewish law is explored. After the dangers from smoking are cited, various precedents in Jewish law are presented as the basis for confronting the matter of smoking. Arguments are suggested for strictly prohibiting smoking. The matter of the effects of smoking on the non-smoker is the subject of much research, and the dangers posed to the innocent bystanders are an added dimension pointing to the hazards of smoking and therefore indicating that it should be prohibited.